Body composition and cardiac dimensions in elite rhythmic gymnasts - Galetta, F.; Franzoni, F.; D`Alessandro, C.; Piazza, M.; Tocchini, L.; Fallahi, P.; Antonelli, A.; Cupisti, F.; Santoro, G. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: Rhythmic gymnasts are often believed to be a population at risk of malnutrition because of their tendency to keep a low weight and a lean appearance for better athletic performance, and because they start intensive training at a very young age. The purpose of this study was to evaluate in adolescent elite gymnasts the effects of physical activity on body composition and cardiac morphology and function.